Perancangan Media Pembelajaran Menggunakan Microsoft Powerpoint dengan Add on Ispring pada Mata Pelajaran Sosiologi di SMAN 01 Kapur IX - Handayani, Sasa; Efriyanti, Liza (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this research is to design the design of Learning Media Using Microsoft Powerpoint with Add on Ispring on Sociology Subjects at Sma N 01 District Kapur IX. The results of observations and interviews that the author conducted on August 28, 2021 to a teacher of sociology subjects at SMAN 01 Kec, Kapur IX, namely Riziz Iskandar S.Pd. He said that many students experienced boredom when learning was taking place in class, this was evident from the way the students were not serious whenlistening to the material he delivered, and many students also did things, such as talking/whispering. with friends beside them . Based on this, the solution given is that is, by designing a learning media. Learning Media Design Research Using Microsoft Powerpoint With Add on Ispring In Sociology Subjects at SMAN 01 Kapur Ix District using research and development (R&D) methods. The system development model uses Luther Sutopo's Multimedia Development Life Cycle development model which consists of 6 stages: Concept, Design, Material Collection, Assembly, Testing, and Distribution. The product tests used in thisstudy are validity tests, practicality tests, and effectiveness tests.‎The results of the product test that the author conducted obtained a validity test from 4 experts with a value of 0.85 with a very valid category, a practicality test from 5 practitioners obtained a value of 0.97 with a very high category, and a test of effectiveness from teachers with a value of 0.85 and from 5 students with a value of 0.86 with the category very effective‎.